The Nexus Between Democracy, Human Development, and Economic Growth: A Provincial Analysis - Ringga, Edi Saputra; Silvia, Vivi (Grimsa Journal of Business and Economics Studies, 2024)
This study aims to investigate the impact of democracy and human development on the economic growth of Aceh Province, Indonesia, especially from a long-term perspective during the period 2010-2020. It employs both static and dynamic approaches, such as Robust Least Squares (RLS), Dynamic OLS (DOLS), Fully-Modified OLS (FMOLS), and Canonical Cointegration Regressions (CCR). This study uses two gross regional domestic products (GRDP) as a proxy for economic growth, namely GRDP migas (referred to as GRDP with the oil and gas sector included) and GRDP nonmigas (referred to as GRDP without the oil and gas sector included). Econometric results indicate that human development has a significant positive impact on economic growth, especially in the long term. Furthermore, the level of democracy also significantly affects economic growth positively. However, this indication is observed in the context where the province’s economic growth is not dependent on natural resources as the primary driver. This study suggests that it is imperative to formulate strategic policies that prioritize human development in education, healthcare, and living standards. This approach aims to foster sustained economic prosperity while also strengthening democratic institutions and promoting good governance. Such efforts are crucial to ensure a stable and conducive environment for provinces to achieve long-term economic development.